Changing uses of wealth stores by rural smallholders: Description of an approach used for longitudinal analysis of livestock transactions in the Sahel - Turner, M. (International Livestock Research Institute, 2004)
In much of rural Africa, livestock represent one of the major individual stores of material wealth. The way in which this wealth is perceived and used will have an important effect on the prospects for sustained agricultural Development and resource management. The study of the changing socio-economic uses of livestock by smallholders is, therefore, highly relevant for agricultural Development. Livestock as individual stores of wealth are unique in that they both reproduce and leave highly tractable genealogical links. These characteristics are not only some of the reasons that make livestock an attractive investment to smallholders but also create an opportunity to research changes in wealth management over time. In livestock, the potential exists for using present wealth to look into the past,. After a review of the multiple roles played by livestock in African communities, this paper describes an approach for a reconstruction of livestock wealth and its management followed by a brief example of its application. Topics of discussion include multiple roles of livestock in rural African communities; livestock as wealth stores; livestock marketing decisions and agricultural Development; livestock marketing resedarch: the need for longitudinal analysis; shifts in species composition of domestic livestock in the sahel; and application of the progeny history techniques in Niger.